Public Private Partnership in State Highways Model Concession Agreement Third Edition: April 2014 - Planning Commission (Planning Commission, 2014)
The network of state and national highways are critical elements of overland connectivity which is essential for development, growth and national integration. The size and quality of the network are key determinants of competitiveness and growth. There is today a broad consensus that a sustained growth rate of about 9% per annum is necessary for India to make progress in eliminating poverty and achieving a quantum jump in the quality of life of its citizens. One of the preconditions for sustaining such a growth rate is the creation of world class infrastructure. However, the investment required for overcoming the deficit in infrastructure quality and quantity is so large that it cannot possibly be met by relying on the public sector alone.
Planning Commission Government Of India
Planning Commission Government of India